2010
DOI: 10.1021/jf903379c
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Plant Secondary Metabolite Decursin by Mycobacterium sp. PYR1001

Abstract: Decursin and its structural isomer decursinol angelate are major secondary metabolites in the root of Angelica gigas Nakai which possess several chemotherapeutic properties. We isolated bacteria capable of transforming decursin and determined metabolites and biotransformation kinetics. Decursinol angelate was not metabolized to any significant extent. Resting cells of Mycobacterium sp. PYR1001 were able to transform decursin. After 24 h incubation, 5 mM of decursin was completely transformed to a metabolite, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, subtle structural difference could lead to different metabolic fate and in vivo activities. Kim et al reported that bacterial enzyme(s) was able to convert only decursin but not DA to DOH [18]. But it was unclear which enzyme was responsible for the hydrolysis of decursin to DOH in the bacteria, and it was also unclear whether human enzymes behave the same as bacterial enzymes or not.…”
mentioning
confidence: 99%
“…However, subtle structural difference could lead to different metabolic fate and in vivo activities. Kim et al reported that bacterial enzyme(s) was able to convert only decursin but not DA to DOH [18]. But it was unclear which enzyme was responsible for the hydrolysis of decursin to DOH in the bacteria, and it was also unclear whether human enzymes behave the same as bacterial enzymes or not.…”
mentioning
confidence: 99%
“…Angelica gigas roots are among the most frequently used natural products in traditional Oriental herbal medicine and dietary supplements (A. gigas Nakai, Apiaceae). They are administered orally, used as a sedative or tonic agent [1][2][3] and marketed as a functional food for womenʼs health care in Europe and the United States [4][5]. Several coumarin derivatives have been isolated from this plant as bioactive compounds [6].…”
mentioning
confidence: 99%
“…However, little is known about the systemic exposure of decursin after administration because the pharmacokinetics of decursin has not been characterized well in vivo as compared to its in vitro pharmacological activity. The only exception is the observation that decursin may be metabolized to decursinol which is also pharmacologically active [5,18,19]. Decursinol has as well various pharmacological activities, including analgesic, serotonergic, antiangiogenic, and anticancer effects [20][21][22][23].…”
mentioning
confidence: 99%
“…This paper identified the esterase activity of Mycobacterium sp. PYR1001, which was able to convert decursin to decursinol, but DA was totally resistant to this conversion [26]. Detailed studies using pure decursin and DA to elucidate their in vivo pharmacokinetic behaviors are needed for future studies.…”
mentioning
confidence: 99%